Economic analysis of advanced biofuels, renewable gases, electrofuels and recycled carbon fuels for the Greek transport sector until 2050. (July 2021) - Paris, Bas; Papadakis, George; Janssen, Rainer; Rutz, Dominik
Abstract: Our economic analysis shows that for Greece no advanced biofuels, renewable gases or electrofuels are currently or will be, until 2050, cost competitive with the production or import costs of fossil fuel equivalents at current fossil fuel prices. This situation holds despite strong learning curve effects for the technologies covered in this study. However, our economic analysis has shown that there are various scenarios and policy interventions that could make some of these fuels cost competitive in Greece with current or slightly higher fossil fuel prices. If the price of crude oil rises significantly to 100 euros per barrel, then recycled carbon fuels and Hydrotreated Vegetable Oil (HVO) can be competitive or close to being economically competitive by 2030 depending on the exact fuel-technology combination. Similarly, injecting biomethane into the natural gas grid becomes cost competitive with natural gas at a tipping fee of 29 euros per tonne in 2020, 21 euros per tonne in 2030, 17 euros per tonne in 2040 and 15 euros per tonne in 2050. Some of the incentives for the production of these advanced fuels could be provided in the form of a landfill tax, higher carbon prices, tax breaks, direct subsidies and high taxes for fossil fuels. Highlights: Challenges exist for the competitiveness of advanced and renewable fuels in Greece. Production costs of advanced biofuels, electrofuels and others for Greece until 2050. No advanced fuels will be cost competitive with fossil fuels in Greece until 2050. A tipping fee can make biomethane and recycled carbon fuels competitive. Support mechanisms can make a range of fuels competitive.